2016
DOI: 10.5624/isd.2016.46.2.133
|View full text |Cite
|
Sign up to set email alerts
|

The impact of reorienting cone-beam computed tomographic images in varied head positions on the coordinates of anatomical landmarks

Abstract: PurposeThe aim of this study was to compare the coordinates of anatomical landmarks on cone-beam computed tomographic (CBCT) images in varied head positions before and after reorientation using image analysis software.Materials and MethodsCBCT images were taken in a normal position and four varied head positions using a dry skull marked with 3 points where gutta percha was fixed. In each of the five radiographic images, reference points were set, 20 anatomical landmarks were identified, and each set of coordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…[18]. Still, most of the references used also relied on the Porion [18,[44][45][46]. Dos Santos et al varied the FHP setups in 3D and noticed that not only did different orientations result in differences in reliability but also that setups dependent on the Porion points and Orbitales were mostly affected [43].…”
Section: Discussionmentioning
confidence: 99%
“…[18]. Still, most of the references used also relied on the Porion [18,[44][45][46]. Dos Santos et al varied the FHP setups in 3D and noticed that not only did different orientations result in differences in reliability but also that setups dependent on the Porion points and Orbitales were mostly affected [43].…”
Section: Discussionmentioning
confidence: 99%
“…Also, in this study, the radiographic measurements of the 3D images were closer to the physical measurements than the 2D slices and 2D projection images [ 22 ]. Kim et al [ 23 ] used coordinates of the anatomical landmarks on the cadaver and concluded that improper patient's head position might result in measurement errors at 5° tilted and rotated positions. The difference in this study as compared to our study could be explained by using 3D image modality and RayScan Symphony® apparatus CBCT machine as compared to panoramic reconstructed images and NewTom CBCT used in our study.…”
Section: Discussionmentioning
confidence: 99%
“…While this may be true, it has some disadvantages such as superimposition of structures and low resolution [28]. In recent years, CBCT has become a diagnostic imaging tool in dentistry since it is a three-dimensional imaging modality with lower radiation exposure and with a higher definition, allowing a clearer view of anatomical areas without the superimposition of structures [29,30]. There is a limited number of studies with CBCT regarding cranial base morphology in CLP patients [9,24].…”
Section: Discussionmentioning
confidence: 99%